2005
DOI: 10.1590/s0006-87052005000100004
|View full text |Cite
|
Sign up to set email alerts
|

Influência do etileno e do 1-MCP na senescência e longevidade das inflorescências de esporinha

Abstract: A aplicação de etileno e do 1-metilciclopropeno (1-MCP) têm efeitos marcantes sobre a abscisão e a longevidade em vaso das inflorescências de esporinha (Consolida ajacis). O etileno acelerou a abscisão das flores em concentrações iguais ou superiores a 1,0 mg L -1 de Ethrel quando pulverizado por duas horas em intervalos de 30 minutos. As concentrações de 100 e 1.000 mg L -1 de Ethrel induziram imediata abscisão das flores, reduzindo a longevidade de 4,4 dias nas flores-controle para 1,8 e 1,2 dias respectivam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Such an effect persists within the plant tissues, even after the STS treatment is over. This is not true for 1-MCP-treatment (Blankenship and Dole, 2003), as can be observed in Consolida ajacis and Pelargonium peltatum flowers, where 1-MCP had a transitory effect in delaying flower wilting and abscission (Cameron and Reid, 2001;Santos et al, 2005). Since 1-MCP was more efficient than STS treatment (Table I), it is probable that E. ibaguense flowers do not develop new ethylene receptors after harvest.…”
Section: Resultsmentioning
confidence: 87%
“…Such an effect persists within the plant tissues, even after the STS treatment is over. This is not true for 1-MCP-treatment (Blankenship and Dole, 2003), as can be observed in Consolida ajacis and Pelargonium peltatum flowers, where 1-MCP had a transitory effect in delaying flower wilting and abscission (Cameron and Reid, 2001;Santos et al, 2005). Since 1-MCP was more efficient than STS treatment (Table I), it is probable that E. ibaguense flowers do not develop new ethylene receptors after harvest.…”
Section: Resultsmentioning
confidence: 87%
“…1methylcyclopropene (1-MCPchemical formula C 4 H 6 ) was discovered in 1995 and it is a non-toxic gaseous compound which inhibits ethylene action by binding itself to hormone receptors in an irreversible manner: the ability of 1-MCP to bind receptors is ten times greater compared to ethylene (Blankenship and Dole, 2003;Ferrante and Francini, 2006;Naing et al, 2022). It has been reported that the vase life of various cut flowers such as carnation (Dianthus cariophyllus L.) (Ichimura and Shimizu, 2002), stock (Matthiola incana) (Çelikel and Reid, 2002), Consolida ajacis (Santos et al, 2005), chrysanthemum (Chrisantemum morifolium Ram.) (Hassan and Gerzson, 2002), snapdragon (Anthirrinum majus L.) (Heffron and Korban, 2022), and Delphinium hybrid (cv.…”
Section: Introductionmentioning
confidence: 99%
“…The abscission and senescence processes may be accelerated by the increase of the ethylene yield (SANTOS et al, 2005), which exerts influence upon the tissue turgidity, accelerating the flower wilt (MAYAK et al, 1977). According to Ciardi and Klee (2001), the sensitivity and response level to the ethylene are dependent on the developmental and perceptive stage of the plant's organ.…”
Section: Introductionmentioning
confidence: 99%